Human rights and social work : towards rights-based practice - Ife, Jim, 1946- (Cambridge, England : Cambridge University Press, 2012)
'Now in its third edition, Human Rights and Social Work explores how the principles of human rights inform contemporary social work practice. Both human rights and social work have traditionally been understood through the lens of an Enlightenment world view. Jim Ife explores the implications of this Enlightenment heritage for social work, and the possibilities of'post-Enlightenment' practice, in a way that is accessible, direct and engaging. The world has changed significantly since the publication of the first edition in 2001 and this book is situated firmly within the context of present-day debates, concerns and crises. It covers the importance of relating human rights to the non-human world, as well as the consequences of political and ecological uncertainty. By examining the evolving nature of human rights, Ife encourages social workers to apply a human rights framework to their practice. Featuring examples, further readings and a glossary, this book enables readers to identify and investigate the important issues and questions arising from human rights and social work. Now more than ever, Human Rights and Social Work is an indispensable resource for students, scholars and practitioners alike.' -Publisher Description.
Human rights in a globalised world -- The three generations of human rights -- Public and private human rights -- Culture and human rights -- Human rights and human needs -- Human rights and obligations -- Ethics and human rights -- Participation in the human rights discourse -- Constructing human rights for social work practice -- Achieving human rights through social work practice -- Respecting human rights in social work practice -- Conclusion: prospects for human rights practice.
Originally published : 2001.
Includes bibliographical references and index.
Keywords: Human rights; Social service -- Moral and ethical aspects; Social workers -- Professional ethics